Current Progress on Butyric Acid Production by Fermentation - Zhang, Chunhui; Yang, Hua; Yang, Fangxiao; Ma, Yujiu (Current microbiology, 2009)
Several issues of butyric acid production with bacteria through fermentation are presented in this review. The current progress including the utilization of butyric acid, the production strains, the metabolic pathway, and regulation are presented in the paper. Process operation modes such as batch, fed-batch, and continuous fermentation are being discussed. Genetic engineering technologies for microbial strain improvement are also being discussed and fermentation systems have been recommended.